The growth performance of common carp (Cyprinus carpio) co-cultured with different vegetable plants in aquaponics system - Sayyid Afdhal El Rahimi; Muammar Mirza Razeky; Adli Waliul Perdana; Dedi Fazriansyah Putra (Depik, 2021)
A 28-days trial was conducted in an aquaponics culture system to determine the effect of the different vegetable plants application on the growth performance and survival rate of common carp (Cyprinus carpio). Common carp seeds were obtained from local fish farmers in Aceh Besar District. A total of 360 common carp fingerlings (size 3-5 cm) were used and placed in 12 containers with the capacity of 80 L each. The study used four treatments, namely A (control), B Kale (Ipomoea aquatica), C Lettuce (Lactuca sativa), and D Pakcoy (Brassica rapa subsp. chinensis), with three replications for each treatment. The result showed that different vegetable plants' applications significantly affected (P 0.05) the absolute weight gain, absolute length gain, and survival rate of common carp fingerlings. The highest value obtained was in treatment B (Ipomoea aquatic) with an absolute weight gain of 3.93 0.28 g, absolute length gain of 3.810.21 cm, and survival rate of 1000.0%, while the lowest was in treatment A (control) with an absolute weight gain of 1.210.76 g, absolute length gain of 1.700.10 cm and survival rate of 910.86%. Water quality was also collected in this study and the parameters during rearing were still within the tolerance limits of common carp rearing. Therefore, it can be concluded that the Kale plant, Ipomoea aquatica is the most recommended vegetable plant to be co-cultured with common carp in the aquaponics system.Keywords:AquaponicsCommon CarpVegetable Plants